MOMENT OF TRUTH FOR WALKING THE TALK AND TALKING THE WALK! REFLECTING ON CRITICAL SUCCESS FACTORS IN PROJECT MANAGEMENT - Percy Siyavizva, Kudzai; Gwakwa, Dr. Milton (The journal of contemporary issues in business and government, 2022)
The contribution of critical success factors to a large extent has been ignored, unacknowledged and taken for granted. The study argues that the successful completion of most projects is a result of the ability of the project team to manage effectively identified critical success factors prior to project launch. The purpose of the review was to assess the extent to which the choice of critical success factors and the management of the factors; accordingly influence project success. The main research question raised by the study is: What are the critical success factors [CSFs] that contribute to project success? A desk review paradigm contributed in defining methodologies and approaches used for final presentation of the researched data. And the study was guided by the project excellence model which is derived from the EFQM-model. A fully fletched literature review was conducted to provide insight to the entire study purpose before primary research was conducted. The key finding from the empirical study is the identification and application[effective management] of critical success factors is fundamental to project success or failure. Independent of the way other studies are conducted, the study confirms that not all success factors applicable in one project will universally apply in the next project. Factors topping the list were top management commitment, resource availability, and project manager’s competence. Further findings show that projects face challenges from various risks, that are not anticipated and that projects provide a series of lessons of the dos and don’ts in a project. The major recommendation is that in order to realise success, project managers should create a critical success factor framework which provide guidance of what is to be focused on and what not to. The study further argues that, there is need to create an integrated focused approach that creates intertwined approaches to project management. Further research is needed on a critical success factors within the construction industry in Botswana. The two distinct study areas, proposed at this juncture, is commissioning of a country wide study for the construction industry and the second study should specifically focus on failure factors in project management, and a nationwide study is recommended